A Comprehensive Survey on Public Auditing for Secure Cloud Storage - Chaudhari, Smita; Kumar Pathuri, Siva (International Journal of Engineering and Technology, 2018)
Cloud computing is the most popular paradigms used today by Industries & individual users to store data. This outsourcing releases user from capital as well as maintenance cost to own their data. But it brings new security challenges such as data integrity & privacy since user has no power of control on his own data. Advances in encryption & authentication techniques has improved security of data at cloud server(CS) but still it is not providing any certificate or assurance about cloud data to user. Most of the times users are not aware of the different controls employed by CS to protect integrity of data. Due to this lack of transparency in system, the user may lose trust on CS. Hence it is a need of user to check integrity of his data at regular intervals. Most of the researchers have given solutions to this problem with the help of cryptography techniques. External parties such as Third-Party Auditors (TPA) are performing audit to verify this remote data on behalf of user. This paper surveys different cryptography mechanisms proposed by different researchers to check integrity of remote data. Finally, we address future research challenges that need to be resolved by researchers to make system more transparent.Â Â